Penggunaan Framework Codeigniter Dalam Pembuatan Web Profil Program Studi Teknik Elektro Universitas Pembangunan Panca Budi Medan - suheri (CV. Hawari, 2023)
The need for a website is very important in an institution in the current digital era, including the Electrical Engineering Study Program at the University of Panca Budi Medan. Through the Merdeka Learning Campus Merdeka (MBKM) program, students can apply their ideas and creativity in developing a website. With the help of the Codeigniter PHP programming framework, creating dynamic websites is easier to use because the CodeIgniter framework implements the Model, View and Controller methods. In developing a website application, a design method is also needed and in this study the author uses the Waterfall method in designing the system.